Precession and obliquity forcing of the freshwater budget over the Mediterranean. (1st September 2015) - Bosmans, J.H.C.; Drijfhout, S.S.; Tuenter, E.; Hilgen, F.J.; Lourens, L.J.; Rohling, E.J.
Abstract: There is strong proxy and model evidence of precession- and obliquity-induced changes in the freshwater budget over the Mediterranean Sea and its borderlands, yet explanations for these changes vary greatly. We investigate the separate precession and obliquity forcing of the freshwater budget over the Mediterranean using a high-resolution coupled climate model, EC-Earth. At times of enhanced insolation seasonality, i.e. minimum precession and maximum obliquity, the area was wetter and the Mediterranean Sea surface was less saline. The latter has been attributed to increased runoff from the south as a consequence of a strengthened North African monsoon, as well as to increased precipitation over the Mediterranean Sea itself. Our results show that both mechanisms play a role in changing the freshwater budget. Increased monsoon runoff occurs in summer during times of enhanced insolation seasonality, especially minimum precession, while increased precipitation is important in winter for both precession and obliquity. We relate changes in winter precipitation to changes in the air-sea temperature difference and subsequently, convective precipitation. The freshening in the minimum precession and maximum obliquity experiments has a strong effect on Mediterranean sea surface salinity and mixed layer depth, thereby likely influencing deep sea circulation and sedimentation at the ocean bottom. Highlights: We separate the effect of precession and obliquity. Both summer monsoonal runoff as well as winter precipitation play a role. For precession, changes in summer monsoonal runoff dominate the freshwater budget. For obliquity, changes in summer runoff and winter precipitation are of similar size. Changes in winter precipitation are related to air-sea temperature differences.